Behavior and design of slender concrete-filled wide rectangular steel tubular columns under axial compression. (October 2021) - Yu, Chao-Qun; Tong, Jing-Zhong; Tong, Gen-Shu
Abstract: In recent years, the concrete-filled wide rectangular steel tubular (CFWRST) columns, whose cross-sectional width-to-depth ratio exceeds 2.0, is widely utilized in medium- and high-rise buildings. The global buckling behavior of CFWRST columns is of great concern in practical projects due to the multi-story fabrication and erection. In this paper, the stability performance of CFWRST columns is investigated. A refined finite element (FE) model is established for numerical simulation, and the ultimate resistances, load-displacement curves and failure modes obtained from FE models are compared with previous test results to verify the validity of the FE model. Main factors, including geometric dimensions, steel tube thickness, steel strength and concrete strength, are studied through parametric analysis. By comparing the typical equations specified in several existing design codes with a large number of numerical simulation results, it is found that Australian code (AS2327-2017), American code (AISC360-2016) and European code (EC4-2004) fail to predict the ultimate resistance of slender CFWRST columns under axial compression, and about half of the prediction results lead to unsafe designs. Meanwhile, the solutions of Chinese codes (GB50936-2014 and GB50017-2017) could conservatively predict the behavior of CFWRST columns within the deviation of 10% for most numerical results. Thus, these two codes are considered to provide valuable references for designing the CFWRST columns in practice.